Impact of Wall Paint Solar Absorptance on CO2 Emissions in Residential Buildings: A Case Study from Bangkok - Rungroj Wongmahasiri; Tarid Wongvorachan; Chaniporn Thampanichwat; Suphat Bunyarittikit (My University, 2024)
Electricity consumption in buildings is a significant contributor to greenhouse gas emissions, which drive climate change. Reducing electricity use in residential buildings, which account for approximately 20% of Thailand’s total electricity consumption, represents a key opportunity for lowering greenhouse gas emissions. The aim of this study was to assess the potential reduction in greenhouse gas emissions through the use of appropriate solar absorptance in wall paint, conducted via an energy simulation using a representative residential building model from Bangkok. The DOE2.1E program was employed to simulate a standard two-story house commonly found in Thailand, with an approximate floor area of 120 square meters. The window-to-wall ratios were set at 10% and 20%, and air conditioning usage was modeled for nighttime hours. External wall paint was assigned varying solar absorption coefficients, ranging from 10% to 90%. Greenhouse gas emissions were calculated by multiplying the simulated annual electricity consumption by the emission factor, expressed in kgCO2eq/kWh, provided by the Thailand Greenhouse Gas Management Organization. The results indicated that adjusting wall paint solar absorptance from 10% to 90% led to a 10% variation in both energy consumption and greenhouse gas emissions, potentially reducing CO2 emissions by approximately 411–456 kgCO2eq per house per year. Therefore, implementing regulations that mandate the use of wall paints with appropriate solar absorption coefficients could significantly reduce greenhouse gas emissions and contribute to environmental protection efforts in Thailand.
Keywords: Urban Heat Island; Absorptance; Urban Heat Island Mitigation